Interior and boundary gradient estimates for solutions to Hessian equations satisfying Neumann boundary conditions. (June 2020) - Dong, Weisong
Abstract: In this paper we study the a priori gradient estimate for admissible solutions to the Neumann problem of fully nonlinear Hessian equations on Riemannian manifolds. We derive the interior gradient estimate for admissible solutions, and then we establish the boundary gradient estimate by reducing it to the interior gradient estimate.